Bioaccumulation and effect of cadmium in the photosynthetic apparatus of Prosopis juliflora. Issue 1 (1st October 2016) - Michel-López, Claudia Yared; Espadas y Gil, Francisco; Fuentes Ortíz, Gabriela; Santamaría, Jorge M.; González-Mendoza, Daniel; Ceceña-Duran, Carlos; Grimaldo Juarez, Onecimo
Abstract: In the present study Prosopis juliflora plants grown in hydroponics solution were exposed to 50, 100 and 1000 μM CdCl2 . The cadmium uptake, transport and toxicity on the photosynthetic activities in the plants were measured at 48 h after starting cadmium treatments. The results showed that the concentration of Cd 2+ in P. juliflora tended to increase with addition of Cd 2+ to hydroponics solution. However, the increase of Cd 2+ in roots and leaves varied largely. In this sense, the accumulation of Cd 2+ in P. juliflora roots increased significantly in proportion with the addition of this metal. In contrast a relatively low level of Cd 2+ transportation index, and bioaccumulation factor were found in P. juliflora at 48 h after of treatments. On the other hand the maximum photochemical efficiency of photosystem II ( Fv / Fm ) and the activity of photosystem II ( Fv/Fo ) ratios in P. juliflora leaf treated with Cd 2+ not showed significantly changes during the experiment. These results suggested that the photosynthetic apparatus of P. juliflora was not the primary target of the Cd 2+ action. Further studies will be focused in understanding the participation of the root system in Prosopis plants with the rhizosphere activation and root adsorption to soil Cd 2+ under natural conditions.